Psychological and Social Impact of Epilepsy: Pediatric and Adolescent Review - Burns, Thomas G.; Loring, David W. (Journal of Pediatric Epilepsy, 2015)
Pediatric epilepsies are associated with psychiatric and behavioral comorbidities that greatly increase disease burden for both patients and their families. In this report, we identify the multiple potential causes contributing to comorbidities including biologic factors associated with epilepsy/epilepsy syndrome, the effects of family dynamics, as well as factors that may be associated with epilepsy management and maintenance and treatment of behavioral comorbidities. Commonalities and differences in the expression of comorbidities across the globe are reported, which provide insight into social and cultural contributions to comorbidity expressions. The challenges faced as children transition into adulthood are many, and this period remains an area that is neglected despite the many challenges patients face during this time. We identify approaches that have been successful in minimizing the contribution of comorbidities, and which are designed to maximize quality of life and include appropriate screening to guide symptom management. The lives of children and adolescents with epilepsy, as well as their families, are enhanced with effective treatment that allows for concepts of concern to both children and adults to be identified and explored as potential starting points for coping with the chronic effects of epilepsy.
Keywords: psychological; social; epilepsy; pediatric; adolescent; behavior